Drosophila SPG12 ortholog, reticulon-like 1, governs presynaptic ER organization and Ca2+ dynamics. - Pérez-Moreno, J.J.; Smith, R.C.; Oliva, M.K.; Gallo, F.; Ojha, S.; Müller, K.H.; O'Kane, C.J. (Journal of Cell Biology, 2023)
Neuronal endoplasmic reticulum (ER) appears continuous throughout the cell. Its shape and continuity are influenced by ER-shaping proteins, mutations in which can cause distal axon degeneration in Hereditary Spastic Paraplegia (HSP). We therefore asked how loss of Rtnl1, a Drosophila ortholog of the human HSP gene RTN2 (SPG12), which encodes an ER-shaping protein, affects ER organization and the function of presynaptic terminals. Loss of Rtnl1 depleted ER membrane markers at Drosophila presynaptic motor terminals and appeared to deplete narrow tubular ER while leaving cisternae largely unaffected, thus suggesting little change in resting Ca2+ storage capacity. Nevertheless, these changes were accompanied by major reductions in activity-evoked Ca2+ fluxes in the cytosol, ER lumen, and mitochondria, as well as reduced evoked and spontaneous neurotransmission. We found that reduced STIM-mediated ER-plasma membrane contacts underlie presynaptic Ca2+ defects in Rtnl1 mutants. Our results show the importance of ER architecture in presynaptic physiology and function, which are therefore potential factors in the pathology of HSP.